Debugging diversity – a pan-continental exploration of the potential of terrestrial blood-feeding leeches as a vertebrate monitoring tool - Schnell, I.; Bohmann, K.; Schultze, S.; Richter, S.; Murray, D.; Sinding, M.; Bass, D.; Cadle, J.; Campbell, M.; Dolch, R.; Edwards, D.; Gray, T.; et al. (Wiley-Blackwell, 2018)
The use of environmental DNA (eDNA) has become an applicable noninvasive tool with which to obtain information about biodiversity. A subdiscipline of eDNA is iDNA (invertebrate-derived DNA), where genetic material ingested by invertebrates is used to characterize the biodiversity of the species that served as hosts. While promising, these techniques are still in their infancy, as they have only been explored on limited numbers of samples from only a single or a few different locations. In this study, we investigate the suitability of iDNA extracted from more than 3,000 haematophagous terrestrial leeches as a tool for detecting a wide range of terrestrial vertebrates across five different geographical regions on three different continents. These regions cover almost the full geographical range of haematophagous terrestrial leeches, thus representing all parts of the world where this method might apply. We identify host taxa through metabarcoding coupled with high-throughput sequencing on Illumina and IonTorrent sequencing platforms to decrease economic costs and workload and thereby make the approach attractive for practitioners in conservation management. We identified hosts in four different taxonomic vertebrate classes: mammals, birds, reptiles and amphibians, belonging to at least 42 different taxonomic families. We find that vertebrate blood ingested by haematophagous terrestrial leeches throughout their distribution is a viable source of DNA with which to examine a wide range of vertebrates. Thus, this study provides encouraging support for the potential of haematophagous terrestrial leeches as a tool for detecting and monitoring terrestrial vertebrate biodiversity.